USING GLOBAL SPORT CEREMONIES TO ACTIVATE HUMAN RIGHTS: AN APPROACH PROMPTED BY THE BEIJING OLYMPIC GAMES. - Patsantaras, Nikolaos (International Sports Law Review Pandektis, 2013)
A closer examination of fundamental Olympic values and symbolic meanings— expressed in the Olympic charter and recognized in Olympic protocol— reveals that they correspond to the basic perceptions in the Declaration of Human Rights. The Olympic project seems to be an ideal vehicle to promote the United Nations values and principles.Conseuently it is important to examine to what extent Olympic action communication is actually used to serve such objectives-goals and to discuss its effectiveness and legitimacy within this framework. Olympic ceremonies, for example, provide an international-global platform of mobilization for individuals, social groups, countries and nations who have been unfairly treated or remain disadvantaged, such as the mass demonstrations around the globe during the Olympic relay from ancient Olympia to Beijing in protest of the violations of human rights in China. This paper disccusses the role of the IOC in accordance to human rights and examines, on a theoretical level, why the Olympic project in general, including the Olympic symbols and ceremonies generate and activate discussions on human rights. This article, as a side effect or by-product reveals the difficulties inherent to the implementation of the human rights project outside of Olympic space and time. One need point out here, with regard to the methodological perspective, that the use of terms such as universalism, internationalism, globalization, enlightenment, nation and nationalism serve as a heuristic approach, in order to link or connect some of their cognitive contents and elementary meanings to the subject.